ZAKAT SEBAGAI INSTRUMEN PEMBANGUNAN EKONOMI KESEJAHTERAAN UMMAT - Andi Bahri S (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2016)
Abstract The obligation of zakat in Islam has a fundamental significance, other than closely related to aspects of divinity, is also closely related to the economic and social problems. Zakat became one of the instruments of collective social welfare achievement. But in reality, the economic potential of this promising and well-being not optimally managed, professional and accountable. This article offers an analysis of the charity as an instrument of economic development of the welfare of the Ummah with the first show reviews historicity zakat. Zakat as an instrument ekonommi and welfare of the community, efforts to optimize its management becomes a necessity because it is one of the pillars of Islam dimension ubudiyyah, ijtimaiyyah and iqtishadiyyah, which can contribute to enhancing the welfare of society and the stranding-rope of love between man (hablunminannas) as well as liaison komunikasi a servant to his Lord (hablunminallah).